Optical trapping enhancement from high density silicon nanohole and nanowire arrays for efficient hybrid organic–inorganic solar cells1. Issue 17 (27th February 2015) - Thiyagu, Subramani; Syu, Hong-Jhang; Hsueh, Chen-Chih; Liu, Chien-Ting; Lin, Tzu-Ching; Lin, Ching-Fuh
<x xml:space="preserve">Abstract</x> The SiNH arrays exhibit excellent light-absorbing structures and higher optical trapping as compared to SiNW arrays, resulting in leading performance power conversion efficiency of 11.25% in the hybrid organic–inorganic solar cells.